ANALYSIS OF WORK DISCIPLINE ON EMPLOYEE PERFORMANCE THROUGH MOTIVATION AS AN INTERVENING VARIABLE (Case Study on OTI Fried Chicken in Semarang City) - Sugiharti, Sugiharti; Ningrum, Dina Dwi; Prasetya, Adhitya Yoga (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This study aims to analyze the relationship between work discipline and employee performance through motivation as an intervening variable. The independent variable analyzed in this study is work discipline. The dependent variable analyzed in this study is employee performance and motivation as an intervening variable.The sample used in this study were employees at OTI Fried Chicken consisting of 119 respondents. Sampling was done by simple random sampling technique. This study uses the Structural Equation Modeling (SEM) analysis method. Data analysis in this study used discriminant validity tests, reliability tests, model quality tests, and hypothesis testing with the help of SmartPLS 3 data processing software. The results of this study indicate that work discipline has a significant positive effect on employee performance. Discipline has a significant positive effect on motivation, motivation has a significant positive effect on employee performance. The other results of this study are that work discipline has a significant positive effect on employee performance through motivation as an intervening variable. Keywords: work discipline, motivation, employee performance